A cross-sectional examination of the mental health of homeless mothers: does the relationship between mothering and mental health vary by duration of homelessness?. Issue 12 (8th December 2014) - Zabkiewicz, Denise M; Patterson, Michelle; Wright, Alexandra
Abstract : Objectives: This study draws on baseline data from the At Home/Chez Soi demonstration project to examine the association between parenting status and mental health among homeless women and whether the association varies by duration of homelessness. Setting: Structured interviews were conducted with participants in five cities across Canada including Moncton, Montreal, Toronto, Vancouver and Winnipeg. Participants: Eligibility criteria included those with legal adult status, with a mental illness, and who lacked a regular, fixed shelter. All 713 women who participated in the larger project were selected for inclusion in this analysis. Measures: The mental health conditions of interest include depression, post-traumatic stress disorder (PTSD), alcohol dependence and substance dependence. Results: The relationship between parenting status and depression, as well as PTSD, varied by duration of homelessness. Among women who had been homeless for less than 2 years, no relationship was found between parenting status and depression, or PTSD. However, among women who had been homeless for 2 or more years, the odds of depression was twice as high among parenting women compared with others (aOR=2.05, p≤0.05). A similar relationship was found between parenting status and PTSD (aOR=2.03, p≤0.05). The odds of substance dependence was found to be 2.62 times greater among parenting women compared with others and this relationship did not vary by duration of homelessness (aOR=2.62; 95% CI 1.86 to 3.69). No relationship was found between parenting and alcohol dependence. Conclusions: Overall, the findings from this study suggest that there is a relationship between long-term homelessness and mothers' risk of poor mental health. Given the multiple demands mothers face, a failure to recognise their unique needs is likely to contribute to intergenerational legacies of homelessness and mental health problems. Trial registration number: World Health Organization's International Clinical Trials Registry Platform (ISRCTN66721740 and ISRCTN57595077 ).